2020
DOI: 10.1186/s13024-020-00402-7
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer’s disease-associated protective Plcγ2-P522R variant promotes immune functions

Abstract: Background Microglia-specific genetic variants are enriched in several neurodegenerative diseases, including Alzheimer’s disease (AD), implicating a central role for alterations of the innate immune system in the disease etiology. A rare coding variant in the PLCG2 gene (rs72824905, p.P522R) expressed in myeloid lineage cells was recently identified and shown to reduce the risk for AD. Methods To assess the role of the protective var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 45 publications
5
79
0
Order By: Relevance
“…In agreement with this finding, BMDMs from mice harbouring the p.P522R variant, were found to have increased basal IP 1 levels when compared to WT [35]. Furthermore, Positron Emission Tomography imaging, using the 18F-FPEA probe to detect Translocator Protein (TSPO) activity, revealed that P522R Knock-In (KI) mice showed an increase in microglial activity when compared to WT littermates [35]. This increased basal activity of the p.P522R variant has only been demonstrated in mouse models to date, and more work is therefore required to determine whether this is also true in human iPSC macrophages from engineered lines, and patient-derived cells.…”
Section: Trem2 and Plcg2 Load-associated Variants Exhibit Opposing Cesupporting
confidence: 78%
See 4 more Smart Citations
“…In agreement with this finding, BMDMs from mice harbouring the p.P522R variant, were found to have increased basal IP 1 levels when compared to WT [35]. Furthermore, Positron Emission Tomography imaging, using the 18F-FPEA probe to detect Translocator Protein (TSPO) activity, revealed that P522R Knock-In (KI) mice showed an increase in microglial activity when compared to WT littermates [35]. This increased basal activity of the p.P522R variant has only been demonstrated in mouse models to date, and more work is therefore required to determine whether this is also true in human iPSC macrophages from engineered lines, and patient-derived cells.…”
Section: Trem2 and Plcg2 Load-associated Variants Exhibit Opposing Cesupporting
confidence: 78%
“…TREM2 p.Q33X Loss of TREM2 expression [43], no studies into effect on microglia phenotype Heterozygous carriers show typical AD pathology with brain atrophy [44] Found in FTD patients [44] TREM2 p.H157Y Increased shedding from microglia [45], leading to phagocytosis deficits [46] Results in an increased risk of Alzheimer's disease, but the clinical phenotype is not characterised [47] TREM2 p.R62H Impaired phagocytosis of Abeta [17] Unclear due to rarity of this variant the P522R mutation might elicit an increase in basal PLCγ2 function [36]. In agreement with this finding, BMDMs from mice harbouring the p.P522R variant, were found to have increased basal IP 1 levels when compared to WT [35]. Furthermore, Positron Emission Tomography imaging, using the 18F-FPEA probe to detect Translocator Protein (TSPO) activity, revealed that P522R Knock-In (KI) mice showed an increase in microglial activity when compared to WT littermates [35].…”
Section: Trem2 and Plcg2 Load-associated Variants Exhibit Opposing Cementioning
confidence: 83%
See 3 more Smart Citations